Personal identity, psychological continuity and externalism - Mandrigin, Alisa (My University, 2007)
According to the psychological account of personal identity for someone to be one and the same person over time Y today must have some of the beliefs, desires, intentions and memories that X had yesterday, as well as some memories of the events that happened to X yesterday. But, on this account, we have the undesirable result that persons can be reduplicated unless we add an additional requirement: Y is uniquely psychologically continuous with X. In an attempt to avoid the problem of reduplication in a different way I invoke arguments for active externalism and the embodied mind. The motivation for exploring embedded and embodied approaches to cognition is that they cast doubt on the easy separation of brain and body which is often taken for granted in the identity literature. With these approaches in mind, the simple assumptions by which brains are imagined to be transplanted into new bodies, and agents are said to be teletransported to new environments should be reviewed. Whilst embodiment provides us with some reasons to re-evaluate our understanding of brain transplant thought experiments, we ultimately see that the nature of teletransportation is consistent with the mind as both extended and embodied.
Keywords: Philosophy; Psychological Continuity; Extended Mind